(untitled) (Mustansiria Dental Journal, 2019)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder affecting women in their reproductive years. It is a complex disorder affects not only general health but also show a reciprocal link with the oral health. C-reactive protein is an acute phase protein which increase their concentration during certain inflammatory disorders and used as a biomarker of inflammation in the body. The aims of this study were to assess the gingival health status among a group of women with polycystic ovary syndrome as well as to estimate the levels of salivary high sensitive c-reactive protein in unstimulated saliva in relation to gingival health condition. Materials and methods: Sixty two females with an age range 20-25 years old and with a body mass index range18.5-24.9 (normal weight) were included in this study. They were divided into two groups; the study group which included thirty one females with polycystic ovary syndrome, those females attended Babylon Teaching Hospital/ Infertility Center with regular cycles, without clinical or biochemical features of hyperandrogenism and ultrasound exclusion of polycystic ovary (without polycystic ovary syndrome). Collection of unstimulated salivary samples was carried out under standardrized conditions, salivary high sensitive creactive protein levels were estimated. Plaque index of Silness and Lӧe (1964) was used to assess dental plaque. While gingival index of Lӧe and Silness (1963) was used to assess gingival inflammation. Results: Results showed that the mean value of plaque index was found to be higher in the control group (1.18±0.03) than that in the study group (1.00±0.08) with statistically highly significant difference (p<0.01).While the mean value of gingival index was higher among the study group (1.52±0.06) than that in the control group (1.31±0.05) with statistically highly significant difference (p<0.01). salivary levels of high sensitive c-reactive protein among women with polycystic ovary syndrome (1061.68±75.41 pg/ml) were found to be higher than that of control (930.51±94.65) with statistically highly significant difference (p<0.01).The results in this study showed that the correlations between salivary high sensitive c-reactive protein with gingival index were statistically highly significant (p<0.01)in women with polycystic ovary syndrome.While statistically no significant correlation between plaque index and high sensitive C-reactive protein(p˃0.05). In order to assess the specificity and sensitivity of the use of salivary high sensitive c-reactive protein as a diagnostic tool, statistical analysis of ReceiverOperative Characteristics Curve (ROC) was used and predictive Value Measurments were done in this study. The results showed that the area under the curve for salivary high sensitive c-reactive protein test was (0.869) with highly significant p-value (p<0.01). The best optimal cut off point for salivary high sensitive c-reactive protein was (1009) with (71%) sensitivity and (96.8%)specificity, indicating a very good predictive capacity for using salivary high sensitive c-reactive protein as a marker for the diagnosis of polycystic ovary syndrome. Conclusions: It was concluded that gingival inflammation was high among women with polycystic ovary syndrome. Furthermore, salivary levels of high sensitive creactive protein were found to be high among women with polycystic ovary syndrome. It was suggested that the measurement of salivary high sencitive creactive protein may be helpful in diagnosis of women with polycystic ovary syndrome.